Meta-analysis of the Efficacy and Safety of Adjunctive Rosuvastatin for Dyslipidemia in Patients with Schizophrenia. Issue 1 (25th July 2018) - Zheng, Wei; Yang, Wei; Zhang, Qing-E; Yang, Xin-Hu; Cai, Dong-Bin; Hu, Jin-Qing; S. Ungvari, Gabor; H. Ng, Chee; De Hert, Marc; Ning, Yu-Ping; Xiang, Yu-Tao
Abstract : Background: Metabolic syndrome in patients with schizophrenia is a major health concern. The efficacy and safety of adjunctive rosuvastatin in treating dyslipidemia were controversial. Aims: To assess the efficacy and safety of adjunctive rosuvastatin for dyslipidemia in patients with schizophrenia. Methods: We systematically searched for relevant controlled clinical trials from the following databases: PubMed, PsycINFO, Cochrane Library, China Knowledge Network, WanFang Database and Chinese Biomedical Database up to September 28, 2017. Standardized mean difference (SMD) and risk ratio (RR) along with their 95% confidence intervals (CIs) were calculated. The quality of the included studies was assessed using the Cochrane risk of bias assessment tool. The GRADE (Grades of Recommendation, Assessment, Development, and Evaluation) system recommendation grading method was used as the reference standard. Results: Four studies ( n =274) comparing rosuvastatin ( n =138) and control ( n =136) groups were identified and analyzed. Adjunctive rosuvastatin showed greater efficacy than control group in low density lipoprotein cholesterol (LDL-C) [4 trials, n =272, SMD: -1.31 (95%CI: -1.93, -0.70), I 2 =81%], total cholesterol (2 trials, n =164, SMD: -2.00 (95%CI: -2.79, -1.21); I 2 =76%) and triglycerides (2 trials, n =164, SMD: -1.05 (95%CI: -1.38, -0.72); I 2 =0%), but not in high density lipoprotein cholesterol (2 trials, n =164, SMD: 0.14 (95%CI: -0.16, 0.45); I 2 =0%). After removing one study without randomization for LDL-C, significance remained [3 trials, n =172, SMD:-1.07 (95%CI: -1.60, -0.53); I 2 =63%]. No significant group differences regarding body weight (3 trials, n =208, SMD: -0.40 (95%CI:-1.29, 0.49); I 2 =89%), body mass index (2 trials, n =164, SMD: -0.34 (95%CI: -1.23, 0.56); I 2 =87%), waist circumference (3 trials, n =208, SMD: -0.43 (95%CI: -1.31, 0.46); I 2 =89%), and fasting glucose (4 trials, n =272, SMD: -0.25 (95%CI: -0.65, 0.15); I 2 =62%) were observed. The adverse reactions and any cause discontinuation rate were similar between the groups. According to the GRADE approach, the evidence levels of main outcomes were rated as "very low" (35.3%) to "low" (64.7%). Of them, the primary outcome (LDL-C) was rated as "very low". Conclusions: The data available on the effectiveness and safety of adjunctive rosuvastatin in treating dyslipidemia for patients with schizophrenia is insufficient to come to a definitive interpretation about its efficacy and safety. Further high quality RCTs with extended treatment duration are warranted to confirm the findings. Review registration: PROSPERO: CRD42017078230